Grandparents and Cultures: Relationships and intergenerational experiences in times of the COVID-19 pandemic (Research, Society and Development, 2023)
In different cultures, the elderly, especially the grandparents, are links of support and solidarity between generations, functioning as anchors of culture, care, education, affection and transmission. This research aimed to analyze reports lived among grandparents, in times of the Covid-19 pandemic. It is a descriptive, exploratory, qualitative and intercultural study, based on semi-structured and open interviews. 37 grandparents from Brazil, Portugal and Uruguay participated in this study. The main results indicate that affective relationships are maintained, but the type of care and activities differ between face-to-face and virtual grandparents.